Multimedia-based Apsimas Learning Media on the Meaning of the Pancasila Precepts in the Community Environment to Improve Students’ Learning Outcomes - Sari, Nur Eka; Witanto, Yuli (International Journal of Elementary Education, 2024)
The limitations of learning media used during learning take place cause students to be discouraged when learning. In learning, obviously, understudies need learning media to assist them with understanding the material sustainable so the advancement of learning media like learning media "Apsimas" (Application of the meaning of the Pancasila precepts) is required. This research aims to produce learning media assisted by articulate storyline 3 in Civics subject material on the meaning of the Pancasila precepts in the community environment of class IV SD which has been tested for validity and reliability and has an effect on student learning outcomes. This research is development research using the ADDIE model. The subjects in this research were: 1 PPKn subject matter expert, 1 learning media expert, 1 practitioner, 9 students for small-scale trials and 17 students for large-scale trials. The data collection methods used were observation, interviews, tests, and questionnaires. Data collection instruments used questionnaires and test questions. The data analysis techniques used are qualitative analysis and quantitative analysis. The data was analyzed using Purwanto's formula to determine the suitability of the material and media being developed. This research produces the learning media "Apsimas" assisted by articulate storyline 3 on PPKn content, material on the meaning of Pancasila principles in the community which has been tested for validity and its reliability and so it is suitable for use in the learning process.